FAKTOR-FAKTOR PEMBENTUK LOYALITAS KONSUMEN PADA GO-JEK DI SEMARANG - Christo Christian Destiyanto; Djoko Setyabudi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
Customer loyalty is a thing that brand really needed to be still remain in bussiness world, including Go-Jek brand which lead the online transportation market-share in Indonesia right now. But, the practical loyalty (customer loyaty to the brand) cannot be found at the customer because of many factors. Based on jak-pat survey, almost 40,89 persen Go-jek user also Grab user. This behavior known as swinger, which the customer switch a brand consumption immediately. This is can be compounded by the no cost status in the process of replacing the use of the brand. Appearance of various assumption about why this swinger behavior happen, is the reason why author want to research about what actually is the forming loyalty factor of Go-jek customers in Semarang. This is an important thing for Gojek because customer loyalty to the brand can be a potential problem that is very detrimental if it is not immediately addressed properly. This research aims to determine what factors form the loyalty of Go-jek customers in Semarang, with population of 139 people who live in Semarang and have used Go-jek and installed the application. Primary data collected by using purposive sampling technique with data collection tools and techniques in questionnaires form and interviews to enrich the obtained information. Based on the data processing results, using the SPSS 20.0 with factor analysis techniques shows that the KMO value (Kaiser-Mayer-Olkin Measure of Sampling Adequancy) and the Barlett's Test method is 0.612 which means more than 0.5 and this research data is possible to test, the Barlett's Test of Sphericity value also has a sig value of 0,000 and from 25 factors (indicators) forming customer loyalty that has been collected through 7 characters through various books and journals research has been reduced to be 7 factors with 62.05 persen of total variance value. The 7 factors consist of Brand quality, Customer experience, Brand image, Selective consume, Personal value, Trusting to brand and Repeat purchase. The conclusion of this research is price factor is the most rapidly changing the customer behavior. Suggestions from the previous author for further research is retesting cases of customer loyalty with variable promotion.